Transforming fish bone waste into hydroxyapatite: insights into heating rate influences during calcination - Mohd Nasir, M. R. H.; C. M. Mardziah; Nik Rozli, N. M.; Abbas, M. K. (UiTM Press, 2025)
In recent years, the exploration of hydroxyapatite (HA) derived from natural resources has witnessed an exponential growth, surpassing the attention given to its synthetic counterparts. Fish bone waste, typically generated from the seafood industry, is often discarded in landfills, which contributes to environmental pollution. Despite its high calcium content, fish bone is still underutilised as a raw material for producing HA. In this study, HA was synthesised via calcination at 1000 ⁰C while heating rates were varied at 2 ⁰C /min and 5 ⁰C /min. The purpose of this study is to produce HA powders from fish bone wastes (HA-fb) and to examine how its characteristics would be affected by altering the heating rate during thermal treatment Thermogravimetric curve revealed a few definite stages of weight loss, mainly due to water evaporation and inorganic compound removal as the temperature increases. XRD analysis demonstrated the appearance of prominent HA and β-TCP peaks in both samples, a typical observation in naturally derived HA powders. In addition, FTIR spectra displayed the emergence of functional groups for hydroxyl, phosphate, and carbonate, further affirming HA formation. FESEM analysis revealed that powders produced at higher heating rates exhibited larger particle sizes and greater agglomeration compared to those synthesised at slower heating rates, confirming the microstructural modification due to the use of different heating rates. The findings from this study would provide valuable information about the effect of exploiting heating rates during the calcination process, particularly on the morphology of the HA-fb powder particles.